Saving exposed titanium mesh cranioplasty using adipocutaneous anterolateral thigh flap: A case series - Mai-Anh Bui; Ngoc-Huy Pham; Trung-Truc Vu (JPRAS Open)
Introduction: Scalp thinning and soft tissue atrophy are significant risk factors for prosthetic material exposure after cranioplasty surgery. Reconstruction of the forehead and scalp to ensure functional coverage and aesthetics continues to be challenging. Patients and Methods: This prospective study assessed 15 patients with titanium mesh material exposure, scalp thinning, and soft tissue atrophy following cranioplasty from 2020 to 2023 to identify contributory factors. All patients underwent reconstruction with free adipocutaneous anterolateral thigh flap to cover skin defects and fill soft tissue. The results were evaluated based on flap survival, coverage, and symmetry after surgery. Results: The average age in the study was 40.46 (range 11–68) years, and the male/female ratio was 9/6. From 2020 to 2023, 15 free adipocutaneous anterolateral thigh flaps were used for reconstruction. Complete flap survival was achieved in 93.3 % (14/15) patients with all titanium mesh implants retained. Symmetry and soft tissue hypoplasia correction was achieved in all 15 cases. Conclusion: Adipocutaneous anterior lateral thigh (ALT) flap is a versatile flap to treat complications following cranioplasty with titanium mesh. The ALT flap provides extensive coverage, reduce the risk of recurrent infections, and create an implant for soft tissue atrophy or skin thinning to restore the scalp's aesthetics